Brain tumours as an unrecognized etiology of infantile epileptic spasms syndrome (IESS): The role of resective epilepsy surgery - Rowan Pentz; Kevin Jones; Ronit Mesterman; Rajesh RamachandranNair; Hiroshi Otsubo; Ayako Ochi; Ivanna Yau; Elizabeth J Donner; George M Ibrahim; Puneet Jain; Robyn Whitney (Epilepsy & Behavior Reports, 2025)
Brain tumours are a rare cause of infantile epileptic spasm syndrome (IESS). Epilepsy surgery may be utilized in refractory IESS due to tumours, although reports are limited. We report an illustrative case of IESS which resolved after tumour resection and performed a literature review of all reported cases of brain tumours causing IESS with hypsarrhythmia. We present a 10-month-old girl with drug-resistant symmetric epileptic spasms (ES). Initial EEG showed symmetric hypsarrhythmia and brain MRI demonstrated a left temporal lobe tumour. Despite non-focal clinical and EEG findings, she underwent tumour resection at 21 months (ganglioglioma). She subsequently had resolution of ES and hypsarrhythmia and developmental gains. Twenty-seven published cases of brain tumours and IESS were reviewed. ES were refractory to medical management in 74 % of reported cases (17/23). ES were symmetric in 17/21 (81 %) and asymmetric in 4/21 (19 %) specified cases. Hypsarrhythmia pattern was asymmetric in 10/20 (50 %) specified cases. Of 21 surviving patients who underwent surgery, 13 (62 %) were seizure free at follow-up and only 1 (5 %) had no improvement. Developmental outcomes were available in 19/21 (90 %) surviving surgical patients and 10/19 had improvements (52 %); 6/19 had normalized development (32 %). Various tumour types were reported and a temporal or frontal location was most common. Brain tumours can cause IESS with or without clinical or EEG focality and are amenable to surgical treatment. We emphasize that the absence of focal signs should not delay surgical assessment for patients with refractory IESS and brain tumours.